(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2017)
The medicinal plants have played a vital role in drug discovery. Many plants are used traditionally for the treatment of different types of viral disorders and other infectious diseases. Herpes simplex virus (HSV) is a ubiquitous organism that causes infections in human populations throughout the world. It causes a variety of diseases ranging in severity from mild to life-threatening. The present study was to evaluate antiviral activity of Hypericum mysorense F. Heyne ethanolic leaf extract against herpes simplex virus type 2 (HSV-2) using HEp-2 cell line. The toxic free concentrations of ethanolic extract were determined using MTT assay, followed by anti HSV-2 activity and a positive control was maintained. 50µg/ml of ethanol extract was observed to be maximum non toxic free concentration against HEp-2 cell line and also exhibited significant inhibitory activity against HSV-2.